Case report: intracranial lesions in a patient with anxiety and depression: tumor recurrence or radiation encephalopathy? - You, Haiping; He, Lin; Ouyang, Zhibo; Yang, Yao; Xie, Shu; Zhou, Jiwei; Zhang, Yun; Shi, Jian (Frontiers in Oncology, 2024)
Radiation encephalopathy (REP) is one of the most common complications of radiotherapy for malignant tumors of the head and neck. Symptoms usually appear months to years following radiotherapy, with headache, insomnia, and memory loss as the main clinical features. We report a patient who was admitted to the hospital with anxiety and depressive disorder and was eventually diagnosed with REP.A 48-year-old patient who had undergone over 2 years of radiotherapy for nasopharyngeal carcinoma was admitted to the Department of Psychosomatic Medicine of our hospital because of recurrent fear, low mood, and waking up from dreams. Magnetic resonance imaging (MRI) revealed a mass in the left temporal lobe with a large peripheral edema. After multidisciplinary consultation, the possibility of tumor recurrence could not be excluded.Resection of the lesioned brain tissue to obtain pathological tissue showed glial cell proliferation and small focal areas of degeneration and necrosis, which indicated that the lesions were inflammatory. Postoperative MRI showed no abnormal signal, and the patient's condition improved.Nasopharyngeal carcinoma patients with a history of radiotherapy and symptoms of increased intracranial pressure and neurological damage should be examined for REP. Furthermore, patients may experience anxiety and depressive disorders as a result of temporal lobe damage caused by REP.